Geologi Situs Benteng Saksi Dan Kuripan Saka, Kabupaten Lampung Selatan - Siswanto; Wahyul Falah; Prasetyaningsih; Nanang Saptono; Endang Widyastuti; Rusyanti; Lia Nuralia (JURNAL PANALUNGTIK, 2021)
The sites of Benteng Saksi and Kuripan Saka are the center of settlement or the capital of Keratuan Darah Putih. The research was conducted in Kuripan Village, Penengahan District, South Lampung Regency. The research objective was to determine the factors causing the sites of Benteng Saksi and Kuripan Saka suitable for settlements. The method used is a field survey and interpretation of geological map data. The results of field observations and mapping showed that the areas of the sites of Benteng Saksi and Kuripan Saka were included in the morphological unit of undulating plains with an average height of 50 m above sea level consisting of tertiary-quaternary and alluvial volcanoclastic deposits. The rock lithology found was Breccia Rocks from the eruption of Rajabasa Volcano and Tufan Sandstones. Based on the analysis of basic physical aspects of the area such as the physical characteristics of the rocks, morphological conditions, availability of water sources, and disaster factors in the area of Benteng Saksi and Kuripan Saka sites, it does not indicate any problems in terms of the basic physical aspects of the area.